Pharmaceutical Branding and Various Attributes Affecting the Prescription Behaviour of Doctors - Reginald Pereira, Savio (Digital Repository of Theses - SSBM Geneva, 2025)
This quantitative, survey-based study investigates five critical factors influencing doctor’s prescription behavior: Medical Representatives, Medication Branding, Medication Costing, Prior Patient Experience or Suggestion and Preferred Pharmaceutical Promotional activity. The theoretical framework used in the analysis include AIDA model, Behavioural Economics Theory, Brand Equity Theory, Diffusion of Innovations Theory, Evidence Based Medicine Theory, Information Processing Theory, Persuation Theory, Rational Choice Theory, Rational Prescribing Model, Shared Decision Making Theory, Signalling Theory and Theory of Planned Behaviour. Utilizing responses from 800 doctors and the theoretical framework, the research applies percentage analysis, chi-square tests, one-sample t-tests to comprehensively assess each factor's impact. For Hypothesis 1, 73.9% of doctors affirmed that medical representatives influence their prescribing decisions. The chi-square test yielded x2= 182.405 (df = 1, p < 0.001), while the t-test reported t = 48.981 (p < 0.001) with a mean difference of 0.761 (95% CI: 0.730.79). The effect size was substantial (Cohen’s d = 1.732), confirming significant influence. Regarding Hypothesis 2, 77.5% acknowledged that Medication Branding affects their prescriptions. Results showed x2= 242.000 (df = 1, p < 0.001) and t= 49.076 (p < 0.001), with a mean difference of 0.725 (95% CI: 0.700.75) and Cohen’s d = 1.735, indicating strong brand impact. For Hypothesis 3, 66.9% agreed that medication cost shapes their prescribing behavior. Statistical analysis revealed x2= 91.125 (df = 1, p < 0.001), t = 49.922 (p < 0.001), mean difference 0.831 (95% CI: 0.800.86) and Cohen’s d = 1.765, emphasizing cost sensitivity. In Hypothesis 4, 72.8% reported that prior patient experience or suggestions influence prescriptions. The chi-square value was x2= 165.620 (df = 1, p < 0.001), t = 49.042 (p < 0.001), with a mean difference of 0.773 (95% CI: 0.740.80) and Cohen’s d = 1.734, confirming patient-driven influence. For Hypothesis 5, 88.1% preferred face-to-face detailing as the primary promotional method. The chi-square test (x2= 1084.907, df = 2, p < 0.001) and t = 129.759 (p < 0.001), with a mean difference of 1.559 (95% CI: 1.541.58) and an exceptional Cohen’s d = 4.588, demonstrated overwhelming preference. Across all 5 hypotheses, null hypotheses were decisively rejected (p < 0.001), with consistently large effect sizes, underscoring that these factors significantly and independently shape doctors’ prescription behavior.